Hydrochemistry of Groundwater in AL Jallam Desert, Salah Al-Din Governorate, Iraq - Farid M Alatar; Alhassan H. Ismail; Muntasir A. Shareef; Corina Boncescu (Journal of Techniques)
The present paper assesses the hydrochemistry of groundwater in AL JALLAM desert and its suitability for human consumption and irrigation. Nine groundwater samples were taken, and they were analyzed for major ions to determine the Piper diagram and Gibbs plot. The results showed that the evaporation process is the primary control of the water quality in the study area. Water Quality Index (WQI) method was utilized to assess the suitability of water for human consumption, whereas different geochemical parameters were used to evaluate the irrigation suitability. Generally, the groundwater in the study area is not suitable for drinking and irrigation. Based on cluster analysis (CA), it was found that two levels of pollution levels in the AL JALLAM desert.